Manganese-nitrogen-based carbon nanofiber composite catalyst as well as preparation method and application thereof

The manganese-nitrogen-based carbon nanofiber composite catalyst prepared by electrospinning and heat treatment solves the problems of low utilization rate of supported catalysts and uneven distribution of metal nanoparticles, and achieves efficient catalytic activity and stability. It is suitable for Advanced oxidation water treatment.

CN119500223APending Publication Date: 2025-02-25WUHAN TEXTILE UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411653218.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the supported catalyst support has low utilization rate and uneven distribution of metal nanoparticles, resulting in low catalytic activity and high preparation cost.

Method used

Manganese-nitrogen-based carbon nanofiber composite catalyst was prepared by dissolving manganese acetylacetone and polyacrylonitrile in N,N-dimethylformamide, electrospinning, pre-oxidation treatment and high-temperature pyrolysis. This method realizes the in-situ growth of metal nanoparticles on carbon nanofibers, and solves the problems of low effective surface area utilization of the carrier and uneven distribution of metal nanoparticles.

Benefits of technology

The prepared Mn-CNF composite catalyst has the characteristics of controllable structure, uniform nanoparticle loading, high catalytic activity and good stability. It is suitable for advanced oxidation water treatment, especially in degrading antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500223A_ABST
    Figure CN119500223A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental catalysis, and provides a manganese-nitrogen-based carbon nanofiber composite catalyst as well as a preparation method and application thereof. The method comprises the following steps: dissolving manganese acetylacetonate and polyacrylonitrile in N, N-dimethylformamide, carrying out electrostatic spinning on a precursor solution, and drying to obtain a metal-polymer nanofiber membrane; the metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis, and manganese / nitrogen-carbon nanofibers are obtained; the molar mass ratio of the manganese acetylacetonate to the polyacrylonitrile is (0.4-1.5) mmol: 1g. According to the preparation method, a uniformly mixed precursor solution is prepared from metal, heteroatoms and a carbon material template through homogeneous phase, then a homogenized fiber composite material is prepared through electrostatic spinning, and finally in-situ growth of metal nanoparticles on carbon nanofibers is achieved through heat treatment. The Mn-CNF catalyst disclosed by the invention has the characteristics of controllable structure, uniform nanoparticle loading and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental catalysis, and in particular to a manganese-nitrogen-based carbon nanofiber composite catalyst and a preparation method and application thereof. Background Art

[0002] At present, the scenario cognition of water pollution control has shifted from macro indicators (COD, TP, TN) to micro indicators (molecular structure of organic matter). At the same time, under the constraints of the "dual carbon" background, how to reduce the energy input in the process of water pollution control has become an issue that cannot be ignored. Among the many pollutant reduction and treatment technologies, environmental catalytic technology that catalytically converts pollutants into harmless substances or recyclable substances occupies an important position and has always attracted much attention. Among them, advanced oxidation technology has developed into an important research direction in the field of organic pollutant control.

[0003] In recent years, with the development of advanced oxidation technology, its scope is no longer limited to oxidation technology based on HO·, but also based on sulfate free radical (SO4 ·- ), chlorine-containing free radicals, superoxide free radicals, singlet oxygen and active high-valent metals (high-valent iron, high-valent manganese) as active oxidizing species are also included in the category of advanced oxidation technology. Among them, the catalytic oxidation technology based on persulfate has the characteristics of strong oxidation ability, long-lasting oxidation effect and environmental friendliness, and has been widely used in the in-situ remediation of soil and groundwater. Therefore, it has natural advantages and potential application value in treating emerging pollutants that are difficult to degrade, persistent, low in content and highly harmful.

[0004] In the field of heterogeneous catalysis, carbon-based materials have attracted extensive attention from researchers due to their unique structure, good acid-base stability, excellent adsorption performance, special electronic properties, and confinement effects. Compared with other heterogeneous activators such as metal oxides, carbon-based materials have better stability and are one of the research hotspots in the field of heterogeneous activation of persulfate. However, single carbon-based catalysts still face problems such as low catalytic activity and high preparation cost. So far, most studies have focused on using metal and heteroatom doping to improve the catalytic activity of carbon materials. For example, through the carrier-metal coordination effect, the exposure of the catalyst active sites can be increased to achieve a synergistic effect of "1+1>2". At the same time, through carrier coordination, the agglomeration effect of metal nanocatalysts can be slowed down. However, the current methods for synthesizing metal-carrier catalysts are mostly two-step methods, that is, first synthesizing a carbon material substrate template, and then loading the metal onto the template through chemical coordination or electrostatic force. The composite catalyst synthesized by the template method faces problems such as low utilization of the effective surface area of ​​the carrier and uneven distribution of metal nanoparticles. At the same time, the two-step template method has a complex process and is not conducive to large-scale engineering applications.

[0005] As a simple and low-cost technology, electrospinning is widely used to prepare various nanofibers. More importantly, by combining electrospinning with other post-processing techniques (such as heat treatment), functional fiber materials with different structures and chemical compositions can be obtained. The derived carbon materials prepared by electrospinning and heat treatment have the advantages of controllable structure and good stability.

[0006] Therefore, it is of great significance to study a method for in-situ synthesis of manganese-nitrogen-based carbon nanofiber composite catalysts based on electrospinning. Summary of the invention

[0007] The purpose of the present invention is to provide a manganese-nitrogen-based carbon nanofiber composite catalyst and its preparation method and application in order to overcome the deficiencies of the prior art, aiming to solve the problems of low utilization rate of supported catalyst carriers and uneven distribution of metal nanoparticles.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a manganese-nitrogen-based carbon nanofiber composite catalyst, comprising the following steps:

[0010] 1) dissolving manganese acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a precursor solution;

[0011] 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane;

[0012] 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain a manganese-nitrogen-based carbon nanofiber composite catalyst;

[0013] In step 1), the molar mass ratio of manganese acetylacetonate to polyacrylonitrile is 0.4-1.5 mmol:1 g.

[0014] Preferably, in step 1), the mass volume ratio of polyacrylonitrile and N,N-dimethylformamide is 1 g:9-11 mL.

[0015] Preferably, the dissolution time in step 1) is 11 to 13 hours, and the dissolution is carried out under stirring conditions at a stirring speed of 900 to 1100 rpm.

[0016] Preferably, the voltage of the electrospinning in step 2) is 14-16 kV, and during the electrospinning process, the propulsion speed of the precursor solution is 0.85-1.15 mL / h, the receiving distance is 14-16 cm, and the relative humidity is ≤50%.

[0017] Preferably, the temperature of the pre-oxidation treatment in step 3) is 190-210° C., and the time of the pre-oxidation treatment is 1.7-2.3 h.

[0018] Preferably, the temperature of the high temperature pyrolysis in step 3) is 780-820° C., and the time of the high temperature pyrolysis is 1.7-2.3 h.

[0019] Preferably, in step 3), the heating rate to the pre-oxidation treatment temperature is 9-11°C / min, and the pre-oxidation treatment is carried out in an air atmosphere; the heating rate to the high-temperature pyrolysis temperature is 4-6°C / min, and the high-temperature pyrolysis is carried out in a nitrogen atmosphere.

[0020] The invention also provides a manganese-nitrogen-based carbon nanofiber composite catalyst prepared by the preparation method.

[0021] The invention also provides the use of the manganese-nitrogen-based carbon nanofiber composite catalyst in activating persulfate to degrade antibiotics.

[0022] The beneficial effects of the present invention include the following:

[0023] 1) The present invention prepares a uniformly mixed precursor solution of metal, heteroatom and carbon material template by homogeneous phase, then prepares a uniform fiber composite material by electrostatic spinning technology, and finally realizes the in-situ growth of metal nanoparticles on carbon nanofibers by heat treatment. The Mn-CNF composite carbon nanocatalyst prepared by the present invention has the characteristics of controllable structure and uniform nanoparticle loading; it provides a new synthesis process for the preparation of heteroatom doped / transition metal-based supported catalysts, and realizes the application in advanced oxidation water treatment.

[0024] 2) The present invention uses less chemical reagents, and polyacrylonitrile can provide both carbon and nitrogen sources, without the need for external carbon and nitrogen sources.

[0025] 3) The process flow of the present invention is simple and easy, and realizes the one-step synthesis of nano metal-carrier catalysts; electrospinning, as a mature textile technology, can produce fiber membranes in large quantities; in the subsequent heat treatment process, the formation of carbon fibers and metal nanoparticles is carried out simultaneously, reducing the traditional two-step template method to a one-step synthesis.

[0026] 4) The metal-nitrogen-based carbon nanocatalyst prepared by the present invention realizes uniform loading of metal nanoparticles and heteroatoms, maximizes the effective surface area of ​​the carrier, and improves the utilization efficiency of metal active sites, and has excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the synthesis route of the manganese-nitrogen-based carbon nanofiber composite catalyst of Examples 1 to 3;

[0028] Figure 2 is a scanning electron microscope image of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1;

[0029] Figure 3 This is a particle size distribution diagram of nanoparticles on the surface of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1;

[0030] Figure 4 This is a high-angle annular dark-field perspective electron microscopy image of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1;

[0031] Figure 5 The electrochemical impedance diagrams of the manganese-nitrogen-based carbon nanofiber composite catalysts of Examples 1 to 3 and the CNF of Comparative Example 1;

[0032] Figure 6 The cyclic voltammetry curves of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 and the CNF of Comparative Example 1;

[0033] Figure 7 The effects of the manganese-nitrogen-based carbon nanofiber composite catalysts of Examples 1 to 3 and the CNF activated persulfate in Comparative Example 1 on the degradation of tetracycline hydrochloride;

[0034] Figure 8 This is a cycle performance diagram of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 for activating persulfate to degrade tetracycline hydrochloride;

[0035] Among them, 1.5Mn-CNF is Example 1, 1Mn-CNF is Example 2, 0.5Mn-CNF is Example 3, and CNF is Comparative Example 1. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a manganese-nitrogen-based carbon nanofiber composite catalyst, comprising the following steps:

[0037] 1) dissolving manganese acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a precursor solution;

[0038] 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane;

[0039] 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain a manganese-nitrogen-based carbon nanofiber composite catalyst.

[0040] In the present invention, the manganese acetylacetonate (C 15 H 21The molar mass ratio of polyacrylonitrile (MnO6) and polyacrylonitrile (PAN) is preferably 0.4-1.5 mmol:1 g, further preferably 0.5-1.2 mmol:1 g, and more preferably 1 mmol:1 g; the mass volume ratio of polyacrylonitrile and N,N-dimethylformamide (DMF) is preferably 1 g:9-11 mL, further preferably 1 g:9.5-10.5 mL, and more preferably 1 g:10 mL.

[0041] In the present invention, the carbon nanofiber composite catalyst with different metal loading amounts is obtained by changing the concentration of manganese acetylacetonate in the mixed solution.

[0042] In the present invention, the molecular weight of polyacrylonitrile is preferably 149,000 to 151,000, more preferably 150,000.

[0043] In the present invention, the dissolution time in step 1) is preferably 11 to 13 hours, more preferably 11.5 to 12.5 hours, and more preferably 12 hours. The dissolution is carried out under stirring conditions, and the stirring speed is preferably 900 to 1100 rpm, more preferably 950 to 1050 rpm, and more preferably 1000 rpm.

[0044] In the present invention, the mixing in step 1) is preferably that manganese acetylacetonate is dissolved in N,N-dimethylformamide, and polyacrylonitrile is slowly added after the complete dissolution; if the polyacrylonitrile is added too quickly, it is easy to form "lumps" in N,N-dimethylformamide. The purpose of slow addition is to prevent the viscosity of some parts in the system from being too high, to ensure that the polyacrylonitrile is completely dissolved, and to form a uniformly mixed precursor solution.

[0045] In the present invention, the voltage of the electrospinning in step 2) is preferably 14 to 16 kV, more preferably 14.5 to 15.5 kV, and more preferably 15 kV. During the electrospinning process, the propulsion speed of the precursor solution is preferably 0.85 to 1.15 mL / h, more preferably 0.9 to 1.1 mL / h, and more preferably 1 mL / h. The receiving distance is preferably 14 to 16 cm, more preferably 14.5 to 15.5 cm, and more preferably 15 cm. The relative humidity is preferably ≤50%, further preferably ≤47%, and more preferably ≤45%.

[0046] In the present invention, the drying temperature is preferably 57 to 63° C., more preferably 58 to 62° C., and more preferably 60° C., and the drying time is preferably 11 to 13 h, and more preferably 12 h.

[0047] In the present invention, a uniform metal-polymer nanofiber membrane is obtained by electrostatic spinning.

[0048] In the present invention, the temperature of the pre-oxidation treatment in step 3) is preferably 190-210°C, more preferably 195-205°C, more preferably 200°C, and the time of the pre-oxidation treatment is preferably 1.7-2.3h, more preferably 2h.

[0049] In the present invention, the temperature of the high-temperature pyrolysis in step 3) is preferably 780-820°C, more preferably 790-810°C, more preferably 800°C, and the time of the high-temperature pyrolysis is preferably 1.7-2.3h, more preferably 2h.

[0050] In the present invention, in step 3), the heating rate for heating to the pre-oxidation treatment temperature is preferably 9-11°C / min, more preferably 9.5-10.5°C / min, and more preferably 10°C / min, and the pre-oxidation treatment is carried out in an air atmosphere; the heating rate for heating to the high-temperature pyrolysis temperature is preferably 4-6°C / min, more preferably 4.5-5.5°C / min, and more preferably 5°C / min, and the high-temperature pyrolysis is carried out in a nitrogen atmosphere.

[0051] In the present invention, the purpose of the pre-oxidation treatment is to allow the metal compound and the high molecular polymer to undergo a sufficient oxidation reaction.

[0052] The chemical reagents in the present invention are all of analytical grade and can be used directly without further purification.

[0053] The invention also provides a manganese-nitrogen-based carbon nanofiber composite catalyst prepared by the preparation method.

[0054] The invention also provides the use of the manganese-nitrogen-based carbon nanofiber composite catalyst in activating persulfate to degrade antibiotics.

[0055] The manganese-nitrogen-based carbon nanofiber composite catalyst of the invention is applied to the field of environmental catalysis, especially to heterogeneous advanced oxidation processes.

[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] 1.5 mmol of manganese acetylacetonate was dissolved in 10 mL of N,N-dimethylformamide, and 1 g of polyacrylonitrile (molecular weight 150,000) was slowly added after stirring at 1000 rpm for 10 min. Then, stirring was continued at 1000 rpm for 12 h at room temperature to form a uniformly mixed precursor solution.

[0059] 8 mL of the precursor solution was added to a 10 mL syringe with a needle gauge of 24G. Electrospinning was performed at a voltage of 15 kV, the propulsion speed of the spinning solution was 1 mL / h, the receiving distance was 15 cm, and the relative humidity was maintained at 45%. The metal-polymer nanofibers were collected with aluminum foil and dried in a blast drying oven at 60°C for 12 h to obtain a Mn-PAN composite nanofiber membrane.

[0060] The Mn-PAN composite nanofiber membrane was pre-oxidized in a muffle furnace, heated to 200°C at a heating rate of 10°C / min in an air atmosphere, and pre-oxidized at 200°C for 2h. Subsequently, the temperature was raised to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and high-temperature pyrolysis was performed at 800°C for 2h. After naturally cooling to room temperature, a manganese-nitrogen-based carbon nanofiber composite catalyst was obtained, which was recorded as 1.5Mn-CNF.

[0061] The relative contents of surface elements of 1.5Mn-CNF of Example 1 are shown in Table 1.

[0062] Table 1 Relative content of surface elements of 1.5Mn-CNF

[0063] Element Type Mass percentage (%) Atomic percentage (%) carbon 49.09 66.23 oxygen 24.21 24.52 nitrogen 1.58 1.83 manganese 25.12 7.42

[0064] Example 2

[0065] The manganese acetylacetonate in Example 1 was changed to 1 mmol, and other conditions were the same as in Example 1 to obtain 1Mn-CNF.

[0066] Example 3

[0067] The manganese acetylacetonate in Example 1 was changed to 0.5 mmol, and other conditions were the same as in Example 1 to obtain 0.5Mn-CNF.

[0068] Example 4

[0069] 1.2 mmol of manganese acetylacetonate was dissolved in 9.5 mL of N,N-dimethylformamide, and 1 g of polyacrylonitrile (molecular weight 149,000) was slowly added after stirring at 950 rpm for 10 min. Then, stirring was continued at 950 rpm for 13 h at room temperature to form a uniformly mixed precursor solution.

[0070] 8 mL of the precursor solution was added to a 10 mL syringe with a needle gauge of 24G. Electrospinning was performed at a voltage of 14.5 kV, the propulsion speed of the spinning solution was 0.9 mL / h, the receiving distance was 14.5 cm, and the relative humidity was maintained at 50%. The metal-polymer nanofibers were collected with aluminum foil and dried in a blast drying oven at 57°C for 13 hours to obtain a Mn-PAN composite nanofiber membrane.

[0071] The Mn-PAN composite nanofiber membrane was pre-oxidized in a muffle furnace, heated to 195°C at a heating rate of 9.5°C / min in an air atmosphere, and pre-oxidized at 195°C for 2.3 hours. Subsequently, the temperature was raised to 790°C at a heating rate of 4.5°C / min in a nitrogen atmosphere, and high-temperature pyrolysis was performed at 790°C for 2.3 hours. After naturally cooling to room temperature, a manganese-nitrogen-based carbon nanofiber composite catalyst was obtained.

[0072] Example 5

[0073] 0.8 mmol of manganese acetylacetonate was dissolved in 10.5 mL of N,N-dimethylformamide, and 1 g of polyacrylonitrile (molecular weight 151000) was slowly added after stirring at 1050 rpm for 10 min. Then, stirring was continued at 1050 rpm for 11 h at room temperature to form a uniformly mixed precursor solution.

[0074] 8 mL of the precursor solution was added to a 10 mL syringe with a needle gauge of 24G. Electrospinning was performed at a voltage of 15.5 kV, the propulsion speed of the spinning solution was 1.1 mL / h, the receiving distance was 15.5 cm, and the relative humidity was maintained at 47%. The metal-polymer nanofibers were collected with aluminum foil and dried in a blast drying oven at 62°C for 12 hours to obtain a Mn-PAN composite nanofiber membrane.

[0075] The Mn-PAN composite nanofiber membrane was pre-oxidized in a muffle furnace, heated to 205°C at a heating rate of 10.5°C / min in an air atmosphere, and pre-oxidized at 205°C for 1.7h. Subsequently, the temperature was raised to 810°C at a heating rate of 5.5°C / min in a nitrogen atmosphere, and high-temperature pyrolysis was performed at 810°C for 1.7h. After naturally cooling to room temperature, a manganese-nitrogen-based carbon nanofiber composite catalyst was obtained.

[0076] Comparative Example 1

[0077] The manganese acetylacetonate in Example 1 was omitted, and other conditions were the same as in Example 1 to obtain nitrogen-based carbon nanofibers, denoted as CNF.

[0078] The schematic diagram of the synthesis route of the manganese-nitrogen-based carbon nanofiber composite catalyst of Examples 1 to 3 is as follows Figure 1 shown.

[0079] The scanning electron microscope image of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 is as follows: Figure 2 As shown, the particle size distribution of the nanoparticles on the surface of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 is as follows Figure 3 The high-angle annular dark-field transmission electron microscopy image of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 is shown in FIG. Figure 4As shown. Figure 2 and Figure 3 It can be seen that the diameter of the carbon nanofibers prepared by the present invention is between 100 and 300 nm, and nanoparticles with an average particle size of 40 nm are uniformly loaded on the fiber surface. Figure 4 High-resolution transmission electron microscopy imaging further demonstrated the average distribution of carbon, oxygen and nitrogen elements on the surface of the nanofibers, and that the nanoparticles were mainly composed of manganese oxides.

[0080] Application Example 1

[0081] The manganese-nitrogen-based carbon nanofiber composite catalysts of Examples 1 to 3 and the CNF of Comparative Example 1 were loaded onto glassy carbon electrodes for electrocatalytic performance testing. The specific operation was as follows: 10 mg of catalyst or nanofiber was added to 970 μL of ethanol solution (270 μL of anhydrous ethanol and 700 μL of water), followed by 30 μL of Nafion solution, and ultrasonicated at a frequency of 100 kHz for 15 min. 5 μL of the obtained sample was added dropwise to a clean glassy carbon electrode and dried at room temperature as a working electrode; a platinum electrode was used as a counter electrode, and an Ag / AgCl electrode was used as a reference electrode.

[0082] Cyclic voltammetry (CV) test: the electrolyte is 0.5 mol / L sodium sulfate aqueous solution, the scan rate is 10-100 mV / s, and the voltage window is -1-1 V;

[0083] Electrochemical impedance spectroscopy (EIS) test: EIS tests were performed on CNF and Mn-CNF catalysts at open circuit voltage with a test frequency range of 0.1 Hz to 1 MHz and an AC amplitude of 10 mV.

[0084] The electrochemical impedance diagrams of the manganese-nitrogen-based carbon nanofiber composite catalysts of Examples 1 to 3 and the CNF of Comparative Example 1 are as follows: Figure 5 As shown in the figure, 0.5Mn-CNF has the smallest radius in the high-frequency region and the largest slope in the low-frequency region, indicating that its charge transfer impedance is the lowest. In particular, compared with CNF, the correlation changes greatly, indicating that the electron transfer rate of Mn-CNF fibers is faster than that of CNF fibers.

[0085] The cyclic voltammetry curves of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 and the CNF of Comparative Example 1 are as follows: Figure 6 As shown, the CV curves show that Mn-CNF has a higher specific capacitance than CNF, thus possessing a better catalytic potential.

[0086] Application Example 2

[0087] The oxidant is persulfate (PDS), the model pollutant is the antibiotic tetracycline hydrochloride (TCH), the catalyst is the manganese-nitrogen-based carbon nanofiber composite catalyst of Examples 1 to 3 and the CNF of Comparative Example 1, and 10 mg of the catalyst and CNF are respectively put into 100 mL of TCH simulated wastewater (the concentration of TCH is 10 mg / L). After uniform dispersion, PDS is added to start the reaction, and the initial concentration of PDS in the system is 1 mmol / L. The concentration change of TCH is detected within a certain period of time. After the reaction is completed, the catalyst is filtered out, washed with ultrapure water, and vacuum dried for the next cycle experiment.

[0088] The effects of the manganese-nitrogen-based carbon nanofiber composite catalysts of Examples 1 to 3 and the CNF activated persulfate in Comparative Example 1 on the degradation of tetracycline hydrochloride are as follows: Figure 7 Compared with CNF, the performance of Mn-CNF in degrading tetracycline hydrochloride by activated persulfate is significantly improved, and the efficiency of degrading tetracycline hydrochloride is consistent with the test results of EIS.

[0089] The cycle performance of the manganese-nitrogen-based carbon nanofiber composite catalyst of Example 1 for the degradation of tetracycline hydrochloride by persulfate activation is shown in the figure below: Figure 8 As shown. After five cycles, the efficiency of Mn-CNF activating PDS to degrade TCH can still reach 70%. At the same time, in the test of actual water bodies (pH is neutral), no manganese ion leaching was detected, which reflects the excellent stability of Mn-CNF.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a manganese-nitrogen-based carbon nanofiber composite catalyst, characterized in that: The following steps are included: 1) dissolving manganese acetylacetonate and polyacrylonitrile in N,N-dimethylformamide to obtain a precursor solution; 2) electrospinning the precursor solution and then drying it to obtain a metal-polymer nanofiber membrane; 3) The metal-polymer nanofiber membrane is sequentially subjected to pre-oxidation treatment and high-temperature pyrolysis to obtain a manganese-nitrogen-based carbon nanofiber composite catalyst; In step 1), the molar mass ratio of manganese acetylacetonate to polyacrylonitrile is 0.4-1.5 mmol:1 g.

2. The preparation method according to claim 1, characterized in that: Step 1) The mass volume ratio of polyacrylonitrile and N,N-dimethylformamide is 1g:9-11mL.

3. The preparation method according to claim 1 or 2, characterized in that: The dissolution time of step 1) is 11 to 13 hours, and the dissolution is carried out under stirring conditions with a stirring speed of 900 to 1100 rpm.

4. The preparation method according to claim 2, characterized in that: Step 2) The voltage of the electrospinning is 14-16 kV. During the electrospinning process, the propulsion speed of the precursor solution is 0.85-1.15 mL / h, the receiving distance is 14-16 cm, and the relative humidity is ≤50%.

5. The preparation method according to claim 3, characterized in that: Step 3) The temperature of the pre-oxidation treatment is 190-210° C., and the time of the pre-oxidation treatment is 1.7-2.3 hours.

6. The preparation method according to claim 4, characterized in that: Step 3) The temperature of the high temperature pyrolysis is 780-820° C., and the time of the high temperature pyrolysis is 1.7-2.3 hours.

7. The preparation method according to claim 5 or 6, characterized in that: In step 3), the heating rate to the pre-oxidation treatment temperature is 9-11°C / min, and the pre-oxidation treatment is carried out in an air atmosphere; the heating rate to the high-temperature pyrolysis temperature is 4-6°C / min, and the high-temperature pyrolysis is carried out in a nitrogen atmosphere.

8. A manganese-nitrogen-based carbon nanofiber composite catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the manganese-nitrogen-based carbon nanofiber composite catalyst according to claim 8 in activating persulfate to degrade antibiotics.